2008
DOI: 10.1073/pnas.0806651105
|View full text |Cite
|
Sign up to set email alerts
|

Electric field-induced direct delivery of proteins by a nanofountain probe

Abstract: We report nanofabrication of protein dot and line patterns using a nanofountain atomic force microscopy probe (NFP). Biomolecules are continuously fed in solution through an integrated microfluidic system, and deposited directly onto a substrate. Deposition is controlled by application of an electric potential of appropriate sign and magnitude between the probe reservoir and substrate. Submicron dot and line molecular patterns were generated with resolution that depended on the magnitude of the applied voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…[4, 17-22] To date, only a few examples of nanopatterning multiple proteins have been reported, and the majority among these examples uses destructive strategies, which require multiple cycles to deposit multiple proteins. As such, the throughput is relatively low and cross-contamination between different proteins is of great concern.…”
mentioning
confidence: 99%
“…[4, 17-22] To date, only a few examples of nanopatterning multiple proteins have been reported, and the majority among these examples uses destructive strategies, which require multiple cycles to deposit multiple proteins. As such, the throughput is relatively low and cross-contamination between different proteins is of great concern.…”
mentioning
confidence: 99%
“…With a structure called the nanofountain AFM probe, Espinoza and co-workers [ 114 ] showed that sub-micrometer features of proteins can be delivered from AFM probes by the application of an electrical potential between the probe reservoir and substrate. An integrated microfl uidic system allows the continuous delivery of materials to the probes.…”
Section: Modifi Cations To the Electrohydrodynamic Jet Printermentioning
confidence: 99%
“…[70][71][72] This approach has demonstrated versatility through the printing of gold colloids, 73 DNA 74 , and proteins. 75 The design has allowed for some unique applications, for example, the injection of single cells with nanoparticles ( Figure 6C). 60 An impressive innovation in recent years has been the advent of lithography using modified scanning ion conductance microscopes.…”
Section: Scanning Probe Lithographymentioning
confidence: 99%